Hemopoietic tissue volume is a heritable trait in the schistosome‐transmitting snail Biomphalaria glabrata. Issue 2 (29th April 2016) - Sullivan, John T.; Beltran, Roxxana V.; Cruz, Brandon C.; Manuel, Rhea A.; White, John K.
Abstract: The anterior pericardial wall or amebocyte‐producing organ (APO) is a site of hemocyte formation in the schistosome‐transmitting snail Biomphalaria glabrata . Histological sections of the APOs of adult schistosome‐resistant Salvador strain snails, and two schistosome‐susceptible M‐line strains, BRI‐M and USF‐M, showed qualitatively differing amounts of hemopoietic tissue (HT), with Salvador>BRI‐M>USF‐M. Adult Salvador snails also had a significantly higher concentration of hemocytes in the hemolymph than the two M‐Line strains. In juvenile snails of the same three strains, measurements of total APO HT volume confirmed the qualitative differences seen in adults, and differences between the three strains were statistically significant. Crosses between Salvador (large HT volume) and USF‐M (small HT volume) show that a large HT volume is dominant in juvenile F1 s. Analysis of the distribution of HT volume among F2 s shows it to be a quantitative trait. Although USF‐M juvenile F0 s had a significantly lower APO HT volume than that of BRI‐M F0 s, they had a significantly higher mitotic index, possibly as a compensatory mechanism. Salvador APO allografts maintained HT volume and mitotic activity equally well in USF‐M and Salvador recipients after 2 weeks, suggesting that the low HT volume in USF‐M snails may result from a developmental defect rather than a lack of HT‐supportive plasma factors.